2019
DOI: 10.1002/jgt.22517
|View full text |Cite
|
Sign up to set email alerts
|

Ore and Chvátal‐type degree conditions for bootstrap percolation from small sets

Abstract: Bootstrap percolation is a deterministic cellular automaton in which vertices of a graph G begin in one of two states, “dormant” or “active.” Given a fixed positive integer r, a dormant vertex becomes active if at any stage it has at least r active neighbors, and it remains active for the duration of the process. Given an initial set of active vertices A, we say that G r‐percolates (from A) if every vertex in G becomes active after some number of steps. Let m(G,r) denote the minimum size of a set A such that G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…One could ask for the conditions on δ(G) that guarantee m(G, r) k for a fixed k r+1. Following the line of inquiry in [9] and [11], one might consider the lower bounds on σ 2 (G) that guarantee that m(G, r) = r for r 3. After this paper was submitted, answers to these questions for k 2r − 2 were given by Wesolek [21].…”
Section: Open Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…One could ask for the conditions on δ(G) that guarantee m(G, r) k for a fixed k r+1. Following the line of inquiry in [9] and [11], one might consider the lower bounds on σ 2 (G) that guarantee that m(G, r) = r for r 3. After this paper was submitted, answers to these questions for k 2r − 2 were given by Wesolek [21].…”
Section: Open Problemsmentioning
confidence: 99%
“…Defining σ 2 (G) to be the minimum sum of degrees of non-adjacent vertices in G, they showed that for a graph on n 2 vertices, if σ 2 (G) n, then m(G, 2) = 2. Subsequently, Dairyko, Ferrara, Lidický, Martin, Pfender, and Uzzell [9] improved this result showing that, except for a list of exceptional graphs that they completely characterized, if σ 2 (G) n − 2, then m(G, 2) = 2. Their results show that the only graph with δ(G) = |V (G)|/2 and m(G, 2) > 2 is the 5-cycle.…”
Section: Introductionmentioning
confidence: 96%
“…A minimum r-percolating set in G is an r-percolating set S of G satisfying m(G, r) = |S|. Bootstrap percolation is very well studied in graphs, see, for example, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Morrison and Noel also proved bounds for multidimensional rectangular grids. Furthermore, the minimal size of a contagious set has been investigated for expander graphs , very dense graphs , random graphs , with additional Ore and Chvátal‐type degree conditions , and in the setting of hypergraphs .…”
Section: Introductionmentioning
confidence: 99%